Impacto Del Cambio Normativo Para Los Fondos Inmobiliarios Listados En Bolsa-Durante El Periodo 2021-2023 Una Experiencia Desde Skandia (2025)
A regulatory change has impacted those investors who have generated an important part of the capital flow of the listed Real Estate Funds and this has resulted in a challenge for this type of Funds, in the search for capital and new investment to continue contributing to the development. of the real estate sector in Colombia, sectors such as offices, health, shopping centers are mainly driven by Real Estate Funds. Additionally, they have entered into a dynamic of raising awareness among investors in the retail segment about the operation, advantages and disadvantages that currently exist in these Funds.